PENINGKATAN HASIL BELAJAR PKn DENGAN PENDEKATAN COOPERATIVE LEARNING TIPE STAD DI SEKOLAH DASAR - Asnidar, Asnidar (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Learning Implementation Plan first cycle with an average of 84% (very good), cycle II with an average of 96% (very good). The observations of teacher activity in the first cycle at an average of 81% (very good), the second cycle is obtained average 92% (very good). The observation execution in terms of student learning in the first cycle at an average of 77% (both aim of this study to describe the improvement of student learning outcomes in learning Civics with type STAD cooperative learning approach in the fourth grade N 12 Kampung Melayu. Research is action class by using qualitative and quantitative approaches. study was conducted a lot of two cycles. observations about), second cycle an average of 92% (very good). Student learning outcomes obtained in the first cycle an average of 74% and in the second cycle gained an average of 83%.   Kata Kunci: Hasil Belajar, PKn, Cooperative Learning, STAD